Advances in Organic Crystal Chemistry Comprehensive Reviews 2015 - Tamura, Rui; Miyata, Mikiji (Springer Japan : Imprint: Springer, 2015)
For the last decade, the topics of organic crystal chemistry have become diversified, and each topic has been substantially advanced in concert with the rapid development of various analytical and measurement techniques for solid-state organic materials. The aim of this book is to systematically summarize and record the recent notable advances in various topics of organic crystal chemistry involving liquid crystals and organic-inorganic hybrid materials that have been achieved mainly in the last 5 years or so. The authors are invited members of the Division of Organic Crystals, The Chemical Society of Japan (CSJ), and prominent invited experts from abroad. This edited volume is planned to be published periodically, at least every 5 years, with contributions by prominent authors in Japan and from abroad.